Developing Students’ Understanding In Learning Passive Voice Trough Cooperative Learning - Yuliana Friska (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The purpose of this study is to see if cooperative learning improves students' grasp of passive voice in the first semester of accounting at Universitas Pamulang. This research is classified as Classroom Action Research (CAR), and it is used to discover and fix a problem related to students' comprehension of passive voice. The writer uses Hopkin's design in this Classroom Action Research. Meanwhile, the information gathered through the interview, questionnaire, observation, and test is being analyzed (pretest and posttest). Based on the outcomes of the study, it can be concluded that the use of cooperative learning in the teaching of passive voice is successful since the success criteria have been satisfied. The results of the posttest 2 reveal that 93.33 percent of the students, received a score of 70 or above. Furthermore, the results of the interview, observation, and questionnaire show a remarkable improvement. In conclusion, the results of the interview, observation, and questionnaire revealed that students' passive voice learning improved significantly after the cooperative learning approach was implemented in the teaching learning process.Keywords: Students' Understanding; Passive Voice; Cooperative Learning.